Improving audit methodology and analysis in commercial enterprises (for example, LLP “Becker”) - Tovma, N. A. (Journal of Economic Research & Business Administration, 2015)
In this article This describes the methodology of the audit operations in trade, highlighted audit planning operations in trade, presented the audit evidence besides the technique of analyzing the operations of trade, special attention is paid to audit procedures during the analysis to trade execution plan analyzed by total turnover, the analysis of the plan turnover, which helps determine whether performed rhythmically plan turnover, whether uniformly satisfied customer demand for products shown assessment inventories, respectivelying to their standards, to calculate the main financial indicators of transactions in the wholesale trade: tovarooborachivaemosti figure in days velocity of circulation of goods and the number of revolutions, the coefficient of variation, showing the degree of irregularity of the plan.